I Crea ‘Te Company Sdn Bhd / Wan Azma Wan Hassan... [et al.] - Wan Hassan, Wan Azma; Ismail, Hirziaty; Nor Hamid, Nor Hafizah; Muhamad Diah, Saldiana Eiza; Muahmnad, Mazlie Astiny (2000)
iCrea’Te Company Sdn Bhd was situated at No 38, Jalan Ibrahim, Sungai Petani Kedah. They had chosen this location because of the facilities provided there. This business is producing readymade curtains which half of the curtains in market nowadays are imported from nearer country around Malaysia. As local entrepreneur, they try to explore the market and try to fulfill customer’s demand. The type of business that they are dealing with is as a manufacturer on producing readymade curtains where they producing two type of fabric cotton and cotton mix wit polyester.